THE IMPORTANCE OF LABORATORY INVESTIGATIONS PRECEDING DENTAL IMPLANT THERAPY - Ion Hurjui; Ion Andrei Hurjui; Ruxandra Maria Hârțan; Diana Popovici; Ionela Lăcrămioara Șerban (Romanian Society of Oral Rehabilitation, 2022)
Patient testing is a mandatory step in preparing for implant surgery and the number of laboratory investigations depends on the patient's health. A thorough history will identify the presence of possible conditions that will require a certain package of laboratory tests. Additional tests and analyzes are prescribed if the patient has chronic pathologies (cardiovascular, endocrine, hematological, lung and digestive diseases, osteoporosis, allergic diseases). Investigations help to identify absolute or relative contraindications, to draw up a treatment plan in the stage of preparation for the dental implant therapy.